(untitled) (Journal of Sciences & Technology, 2021)
This paper presents the fatigue life behavior of upper arm suspension under cyclic loading. The main objectives are to predict the fatigue life of the component using strain life approach, to identify the critical location and to select the suitable materials for the suspension arm.To conduct this analysis three aluminum alloys were selected for the suspension arm, to do so CAD model of upper arm is designed in Solid Works and imported in a finite element ANSYS code. The upper arm was subjected to constant amplitude loading in z direction and boundary conditions were applied at the end of bushing. Tetrahedral elements gives enhanced results as compared to other types of elements, therefore the elements used in this analysis is (TET 10); the maximum principal stress is considered in the linear static stress analysis and the critical location was considered at node 63754.The finite element model and analysis were performed utilizing the finite element analysis code. Finally, damage is evaluated to the remaining capacity of life and then the stress and strain at the critical region are estimated. From the fatigue analysis Aluminum alloys 7175-T73 and 2014-T6 presents a similar behavior compared to 6061-T6 , in this case of study these lather are considered to be the materials of choice to manufacture the suspension arms; but 7175-T73 Aluminum alloys remains the material with a better resistance to fatigue.